Modulation of orexigenic and anorexigenic peptides gene expression in the rat DVC and hypothalamus by acute immobilization stress - Chigr, Fatiha; Rachidi, Fatima; Tardivel, Catherine; Najimi, Mohamed; Moyse, Emmanuel (Frontiers in Cellular Neuroscience, 2014)
We studied the long term effects of a single exposure to immobilization stress (IS) (1 hour) on the expression of anorexigenic (Pro-opiomelanocortin: POMC and cocaine amphetamine related transcript: CART) and orexigenic (neuropeptide Y:NPY, Agouti related peptide: AgRP) factors in hypothalamus and dorso vagal complex (DVC). We showed, by using RT-PCR that in the hypothalamus, that the mRNAs of POMC and CART were up-regulated at the end of IS and up to 24 hours. This up regulation persists until 48-72h after IS for CART only. In the DVC, their expressions peak significantly at 24h post stress and decline afterwards; CART mRNA is down regulated after 48h post stress. NPY and AgRP mRNAs show a gradual increase just after the end of IS. The up regulation is significant only at 24 hours after stress for AgRP but remains significantly higher for NPY compared to controls. In DVC, the mRNAs of the two factors show generally a similar post stress pattern. A significant increase jut after the end of IS of rats which persists up to 24 hours after is firstly noticed. The levels tend then to reach the basal levels although, they were slightly but significantly higher up to 72 hours after stress for mRNA NPY. The comparison between the expression profiles of anorexigenic and the two orexigenic peptides investigated shows the presence of a parallelism between that of POMC and AgRP and that of CART and NPY when each brain region (hypothalamus and DVC) is considered separately. It seems that any surge in the expression of each anorexigenic factor stimulates the expression of those of corresponding and appropriated orexigenic one. These last reactions from orexigenic peptides tend to attenuate the anorexigenic effects of CART and POMC and by consequent to abolish the anorexia state generated by stress.